Magnetic structures of the low temperature phase of Mn3(VO4)2 – towards understanding magnetic ordering between adjacent Kagomé layers. Issue 1 (20th November 2015) - Clemens, Oliver; Rohrer, Jochen; Nénert, Gwilherm
Abstract : The magnetic structures of the low-temperature phase of Mn3 (VO4 )2 are solved and discussed in this article. Abstract : In this article we report on a detailed analysis of the magnetic structures of the magnetic phases of the low temperature (lt-) phase of Mn3 (VO4 )2 (Mn3 V2 O8 ) with a Kagomé staircase structure determined by means of powder neutron diffraction. Two magnetic transitions were found at ∼25 K (HT1 phase, Cmc ′ a ′) and ∼17 K (LT1 phase, Pmc ′ a ′), in excellent agreement with previous reports. The LT1 phase is characterized by commensurate magnetic ordering of the magnetic moments on two magnetic sites of the Mn1 a / b (2 a + 2 d ) and Mn2 (8 i ) ions of the nuclear structure (where for the latter site two different overall orientations of magnetic moments within the ab -plane (Mn2 a and Mn2 b ) can be distinguished. This results in mainly antiferromagnetic interactions between edge-sharing Mn-octahedra within the Kagomé planes. The HT1 phase is characterised by strong spin frustration resulting from the loss of ordering of the magnetic moments of Mn2 a / b ions along the b -axis. Both magnetic structures are in agreement with the previously reported ferrimagnetic properties of lt-Mn3 (VO4 )2 and shed light on the magnetic phase diagram of the compound reported previously. The magnetic structures are discussed with respect to superexchange interaction pathways within the Kagomé layers, which appear to be predominantly antiferromagnetic. The magnetic structures of Mn3 (VO4 )2 are different compared to those reported for Ni3 (VO4 )2 and Co3 (VO4 )2 and represent an unique commensurate way out of spin frustration for compounds with strong antiferromagnetic superexchange interactions within the Kagomé layers. Additionally, we derive a superexchange model, which will be called redox-mediated M–M ′ (d 0 )–M superexchange and which can help to understand the exclusively ferromagnetic ordering of adjacent Kagomé layers found only for lt-Mn3 (VO4 )2 .